2018
DOI: 10.1017/thg.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

Adult Empathy: Possible Gender Differences in Gene-Environment Architecture for Cognitive and Emotional Components in a Large Italian Twin Sample

Abstract: Empathy plays a central role in prosocial behavior and human cooperation. Very few twin researchers have investigated innate and environmental effects in adult empathy, and twin research on gender differences in these effects is sparse. The goal of this study was to examine innate and environmental influences on three components of an empathy scale frequently used with adults - the expression of cognitive (CE), emotional (EE), and social skills (SS) empathy - and to explore gender differences in the influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…However, it has been observed that such trend is not representative of the empirical data obtained by some authors which reflect conflicting results. 22,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] On the other hand, gender empathy has been studied in homozygotic and dizygotic twins 46 and possible gender-specific innate and environmental influences on empathy and its cognitive and emotional components were found. In relation to the differences found in the present work (higher in women) in the values of Empathy and PA, and, in particular with the PA dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been observed that such trend is not representative of the empirical data obtained by some authors which reflect conflicting results. 22,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] On the other hand, gender empathy has been studied in homozygotic and dizygotic twins 46 and possible gender-specific innate and environmental influences on empathy and its cognitive and emotional components were found. In relation to the differences found in the present work (higher in women) in the values of Empathy and PA, and, in particular with the PA dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy is influenced by multiple factors, as stated above, 8,16,17,[46][47][48] and this situation should also be considered to explain the differences found between the specialties studied in this work. The dentist is one of the health workers who experiences more physical and mental illness.…”
Section: It Is An Important Finding That the Dimensions CC And Puttingmentioning
confidence: 99%
“…So far, very few twin studies have investigated innate and environmental effects in adult empathy and, even fewer have investigated possible gender differences in these effects. A twin study (Toccaceli et al, 2018) was conducted to examine innate and environmental influences on three components (cognitive, emotional and social skills) of an empathy scale frequently used with adults, the Empathy Quotient by Baron-Cohen & Wheelwright (2004), and to explore gender differences in these influences. Women's empathy (and its subdimensions as well) seemed to be predominantly driven by genetic factors and individual (non-shared) experiences, whereas for males, no genetic contribution and substantial influences of both shared and individual environmental effects emerged.…”
Section: From Children To Adults: Behavior Personality and Brain Funmentioning
confidence: 99%
“…In line with this, recent studies have questioned the existence of such rigid differences in empathy between men and women. Sex differences could result from the interaction of multiple factors, such as social learning, genetic predisposition, evolutionary underpinnings, and interpersonal styles [ 61 , 62 ]. The women in the present study scored higher on the emotional components; as these are more dependent on neurochemical processes, it is intuitive for sex differences to exist.…”
Section: Discussionmentioning
confidence: 99%